Tetrahydrobiopterin in Myalgic Encephalomyelitis/Chronic Fatigue Syndrome: A Friend or Foe? - A. F. M. Towheedur Rahman; Anna Benko; Sarojini Bulbule; Carl Gunnar Gottschalk; Leggy A. Arnold; Avik Roy (Biomolecules)
Myalgic Encephalomyelitis or Chronic Fatigue Syndrome (ME/CFS) is a chronic multisystem disease characterized by severe muscle fatigue, pain, dizziness, and brain fog. The two most common symptoms are post-exertional malaise (PEM) and orthostatic intolerance (OI). ME/CFS patients with OI (ME+OI) suffer from dizziness or faintness due to a sudden drop in blood pressure while maintaining an upright posture. Clinical research has demonstrated that patients with OI display severe cardiovascular abnormalities resulting in reduced effective blood flow in the cerebral blood vessels. However, despite intense investigation, it is not known why the effective cerebral blood flow is reduced in OI patients. Based on our recent findings, we observed that tetrahydrobiopterin (BH4) metabolism was highly dysregulated in ME+OI patients. In the current review article, we attempted to summarize our recent findings on BH4 metabolism to shed light on the molecular mechanisms of OI.